The Role of Colour Doppler Ultrasonography in the Diagnosis of Fascial Space Infections - A Cross Sectional Study - Nisha V., Aarthi (JCDR Research and Publications (P) Limited, 2013)
Aims and Objectives: (1) To evaluate the role of ultrasonography with colour Doppler in the diagnosis of fascial space infections, (2) To determine the nature, size and extent of the odontogenic infections which involve the primary and secondary fascial spaces of the maxilla and the mandible (3) To evaluate the sensitivity of ultrasonography in determining whether the inflammatory process is in a stage of cellulitis or abscess and to thus determine the appropriate time for a surgical intervention during the course of the infection and to correlate the clinical and radiographic findings with the ultrasonographic findings and (4) to determine the treatment plan. Methodology: Thirty four patients with odontogenic infections which involved the superficial and the deep fascial spaces of the head and neck were subjected to ultrasonographic examinations over the suspected area in the transverse and axial directions to determine the stage of the infection, its anatomic location and the treatment plan. Results: Ultrasonography showed 95.7% sensitivity and 100% specificity as compared to the clinical and radiographic diagnoses and it proved to be an effective investigation modality in the diagnosis of fascial space infections.